2015
DOI: 10.1242/jcs.173435
|View full text |Cite
|
Sign up to set email alerts
|

The cytolinker plectin regulates nuclear mechanotransduction in keratinocytes

Abstract: The transmission of mechanical forces to the nucleus is important for intracellular positioning, mitosis and cell motility, yet the contribution of specific components of the cytoskeleton to nuclear mechanotransduction remains unclear. In this study, we examine how crosstalk between the cytolinker plectin and F-actin controls keratin network organisation and the 3D nuclear morphology of keratinocytes. Using micro-patterned surfaces to precisely manipulate cell shape, we find that cell adhesion and spreading re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 69 publications
6
33
0
Order By: Relevance
“…This is the case since plectin, a cytolinker which binds nesprin-3 at the nuclear envelope43, links actomyosin to cytoplasmic intermediate filaments such as vimentin4445. That the nucleus responds to mechanical feedback from an integrated cytoskeletal network of various interconnected filaments is supported by multiple previous studies that have demonstrated roles for both actomyosin and intermediate filaments in modulation of nuclear organization and movement12153946474849. Plectin, which interacts with plasma membrane bound factors such as integrins, spectrin and PIP250, is also a candidate linker for the implied coupling between the plasma membrane and the nucleus, suggested by our data.…”
Section: Discussionmentioning
confidence: 83%
“…This is the case since plectin, a cytolinker which binds nesprin-3 at the nuclear envelope43, links actomyosin to cytoplasmic intermediate filaments such as vimentin4445. That the nucleus responds to mechanical feedback from an integrated cytoskeletal network of various interconnected filaments is supported by multiple previous studies that have demonstrated roles for both actomyosin and intermediate filaments in modulation of nuclear organization and movement12153946474849. Plectin, which interacts with plasma membrane bound factors such as integrins, spectrin and PIP250, is also a candidate linker for the implied coupling between the plasma membrane and the nucleus, suggested by our data.…”
Section: Discussionmentioning
confidence: 83%
“…On plectin knockdown, actomyosin-dependent nuclear deformation occurred, whereas direct interactions between keratins and the nuclear envelope were not required. Instead, plectin down-regulation reduced KIF density in the nuclear perimeter (Almeida et al 2015). Possibly, plectin acts as a mechanosensor as it contains a cryptic SH3 domain in the fifth spectrin repeat of its plakin domain.…”
Section: Intrinsic Keratin Properties and Associated Proteins As Detementioning
confidence: 96%
“…On the other hand, the microtubule network has been shown to support nuclear rotation and repositioning, highlighting its mechanical link with the nucleus via microtubule-associated motor proteins and members of the nesprin family 17, 18 . Finally, the intermediate filament network has been recently proposed as an additional player in the mechanical regulation of nuclear shape in keratin-rich cells 19 . It should be pointed out that the findings obtained in the studies presented so far have been based on the use of knock-out cell lines or the selective inhibition/depolymerisation of cytoskeletal proteins of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the elements of the cytoskeleton do not exist in isolation inside the cellular milieu, instead they are intimately linked physically as well as in their co-regulation. Accordingly, disruption of one network is likely to alter the organization and mechanical state of another and vice versa 19, 20 . In a similar fashion, the popular use of micropatterning to modulate the actin cytoskeleton by limiting cell spread area 13, 21, 22 fails to acknowledge that the organization of the other cytoskeletal networks is most likely disturbed too.…”
Section: Introductionmentioning
confidence: 99%